Sound pressure levels in emission of percussion instruments during training sessions - JAROSZEWSKI, A.; ROGOWSKI, P.; RAKOWSKI, A. (Archives of Acoustics, 2000)
Sounds of selected percussion instruments played in individual training sessions of students-percussion players were recorded and analysed. In statistical signal analysis the "impulsiveness" in terms of Lmax-Leq and in terms of kurtosis, as an alternative measure were determined. Signal recording and spectral analysis were performed in the frequency range up to 96 kHz.